Experimental free convection-induced flow inside an unevenly heated inclined duct in the transient and laminar regimes; application to PV-DSF installations - Fatnassi, Sarra; Abidi-Saad, Aissa; Bouraoui, Mohamed; Beaumont, Fabien; Bogard, Fabien; Murer, Sébastien; Polidori, Guillaume (Heat and Mass Transfer, 2022)
In this article, Particle Image Velocimetry (PIV) experiments are carried out in an attempt to predict the morphology of fluid flow induced by natural convection in an Inclined PhotoVoltaic Double Skin Façade (IPVDSF) during transient and laminar regimes. These experiments were performed on an unevenly heated channel with an aspect ratio Ar = 5.2 and heated with UHF equal to 445 W/m2, corresponding to a modified Rayleigh number Ram = 2.2 106. It should be noted that the study is carried out under both realistic geometrical and environmental conditions. Seeking to simulate the impact of the surroundings, the unevenly heated channel is immersed within a water reservoir. Besides the investigations on fluid flow behavior, the purpose of this work is to plug the gap between baseline data to be used for numerical findings accuracy and the data helping in design development of such systems, while keeping in mind aesthetics as well as PhotoVoltaic (PV) efficiency enhancement aspects. The considered dispositions of the PVDSF duct are a negative slope (-10°) and positive slope (+ 10°), compared with the baseline case of vertical slope 0°. Results are described by streamlines and velocity field. The main observation is a complicated topological flow morphology within the PVDSF channel, but it should also be noted that the slope has a significant effect on flow and velocity fields for both flow regimes. Excellent agreement is finally found between the current experimental results and the theoretical ones.